Development of Information Processing Learning Design to Empower Communication and Collaboration Skills of Prospective Biology Teacher Students - Jamaluddin Jamaluddin; A. Wahab Jufri; Agus Ramdani (Jurnal Penelitian Pendidikan IPA, 2024)
Communication skills and collaboration skills are two of the 21st century soft skills that are very important to be mastered by prospective biology teacher students. Therefore, it is necessary to design learning that is oriented towards empowering these skills. This study aims to develop a learning design based on information processing theory, and to test its effectiveness on the communication skills and collaboration skills of prospective biology teacher students at the FKIP, Mataram University. This study is a development research whose procedure uses the ADDIE development research model. The product produced in this study is a learning design based on information processing theory consisting of RPS, RTM and Student Learning Journals. The results of the validation by biology learning experts stated that the learning design was declared valid. The results of the learning design effectiveness test showed that the application of learning design in the biology learning strategy course was effective for communication skills, collaboration skills, and students' understanding of concepts. Based on the validation results, and the effectiveness test of the application of learning design, it can be stated that learning design based on information processing theory can be used as one of the innovative learning designs that is oriented towards strengthening soft skills, especially for students' communication skills and collaboration skills